2012
DOI: 10.14214/sf.56
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of stem attributes by combining airborne laser scanning and measurements from harvesters

Abstract: In this study, a new method was validated for the first time that predicts stem attributes for a forest area without any manual measurements of tree stems by combining harvester measurements and Airborne Laser Scanning (ALS) data. A new algorithm for automatic segmentation of tree crowns from ALS data based on tree crown models was developed. The test site was located in boreal forest (64º06'N, 19º10'E) dominated by Norway spruce (Picea abies) and Scots Pine (Pinus sylvestris).The trees were harvested on field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 17 publications
5
54
0
Order By: Relevance
“…However, entirely different estimation and operation models are required for tasks that would extend our knowledge available from a forest, compared to the traditional, subjective forest mapping inventories. For example, in ABA, stem-quality attributes required by the forest industry, such as species-specific timber assortments, cannot be obtained accurately [5,[8][9][10]. Single tree-level information would be required to solve the above-mentioned limitations [11,12].…”
Section: Towards Precision Forestrymentioning
confidence: 99%
“…However, entirely different estimation and operation models are required for tasks that would extend our knowledge available from a forest, compared to the traditional, subjective forest mapping inventories. For example, in ABA, stem-quality attributes required by the forest industry, such as species-specific timber assortments, cannot be obtained accurately [5,[8][9][10]. Single tree-level information would be required to solve the above-mentioned limitations [11,12].…”
Section: Towards Precision Forestrymentioning
confidence: 99%
“…In general, the ITC approach is at its best in single-layered mature stands. Holmgren et al [16] showed that if the harvester measurements are used as reference data for ALS-based tree-level inventories, highly accurate estimates can be obtained. Their imputation accuracies (root mean squared error percentage RMSE-%) for stem volume, mean tree height, mean stem diameter, and stem density were 11%, 8%, 12%, and 19%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Harvester data have been used in combination with conventional inventory data to develop harvester-based forest inventory systems (Stendahl and Dahlin 2002;Murphy et al 2006;Holopainen et al 2010) and with remote sensing imagery and LiDAR data to predict attributes of individual trees, stands and forests (Rasinmäki and Melkas 2005;Holmgren et al 2012;Söderberg 2015), product recovery (Peuhkurinen et al 2008;Barth and Holmgren 2013;Barth et al 2015), and wood properties (Möller et al 2003). Such combined use of harvester data creates a representation of the entire forest area in great detail, allowing forest managers to see what trees are standing where and to predict what volume or value of a certain product or a product mix the forest can yield.…”
Section: Introductionmentioning
confidence: 99%